Health shocks and shifts in livelihood systems of natural resources-based communities in the Congo Basin: evidence from the Campo Ma'an National Park, Cameroon - Kometa, Raoul Ndikebeng; Wanie, Clarkson Mvo; Makoley, Nkumbesone Essone; Kimengsi, Jude Ndzifon (Frontiers in Sustainable Resource Management, 2025)
The sheer impacts of communicable and non-communicable health shocks globally are increasingly visible on social, economic, and natural systems, with growing concerns, especially in sub-Saharan Africa. Despite this salience, micro-scale evidence on how health shocks induce shifts in resource-based livelihoods is lacking. This is particularly intense in the Campo Ma'an National Park communities. Thus, this study examines the extent to which livelihood systems have been reshaped by health shocks, including communicable and non-communicable diseases, in the Campo Ma'an National Park communities, particularly over the past 5 years. To achieve this aim, 200 natural resources dependent households were randomly sampled around the Campo Ma'an National Park, complemented by expert interviews (N = 6), Key Informant Interviews (N = 6) and Focus Group Discussions (N = 4). Data were analyzed descriptively using percentages, frequencies, and charts and inferentially using the Chi-Square Test. The results reveal significant differences in financial capital compared to all other capitals (X2 = 7.356, p =0.059), which is significantly higher for the contribution of communicable diseases compared to non-communicable diseases. Additionally, no significant difference was observed in the accumulation of social, natural and human capital comparing the results due to Communicable and Non-Communicable Health Shocks (p > 0.1). Health shocks are construed as unpredictable/unexpected changes or occurrences in human health, involving communicable diseases such as Malaria, STIs (HIV and AIDS), Tuberculosis, COVID-19, neglected tropical diseases and/or non-communicable diseases like Cardiovascular diseases, Hypertension, Cancer, Diabetes, Mental health ailments, amongst others. livelihood entails the stores, resources, claims, and access (assets, capabilities, and activities) required to sustain a living. The chi-square test indicates that communicable diseases contributed more to changes in livelihood capitals, especially financial capital, than non-communicable diseases, disrupting the normal functioning of individuals, households and communities, with severe impacts visible on human wellbeing as well as livelihood systems. Shifts in livelihood systems were further triggered by actor dynamics as conflicting interests and power distribution among local communities, government agencies, the private sector and NGOs, influenced livelihood strategies in terms of livelihood diversification, intensification and/or business-as-usual scenario. This informs the vulnerable dimension of the Sustainable Livelihoods Framework.